The Carbapenemase BKC-1 from Klebsiella pneumoniae Is Adapted for Translocation by Both the Tat and Sec Translocons - Manasa Bharathwaj (American Society for Microbiology, 2021)
Bacteria can readily acquire plasmids via lateral gene transfer (LGT). These plasmids can carry genes for virulence and antimicrobial resistance (AMR).